Penerapan Syslog Monitoring Jaringan Menggunakan The Dude dan EoIP Tunnel - Taufik Rahman; Herman Kuswanto (Politeknik Harapan Bersama, 2019)
In the era of technology 4.0, the use of the internet is very quickly followed by the development of increasingly complex supporting devices, each activity of devices that are connected or disconnected in the network will send or issue messages that will affect the devices around them because each device has a different role on the network . Messages issued by the device must be considered, especially by network administrators. In general, the message is stored locally in the memory or drive of the device, it will be very dangerous if the device is turned off so the message is lost. or messages sent over the network to a centralized server. One technology that can be used to collect messages is the Dude application through a virtual private network, EoIP Tunnel. From the results of research that has been done, it can be said that system messages (syslog) from computer network devices both internet or intranet using the dude server can be implemented and are very safe because all activities that occur on switches are manageable, access points and routers on campus will be stored. When problems occur regarding network connections, syslog on the dude server can be opened using wordpad or similar applications. Virtual tunnel network, EoIP Tunnel can be configured on MikroTik routers by network administrators, so that syslog can be sent and entered into the dude server. EoIP tunnel development can be used or running simultaneously with OSPF routing.